Tectonics of collision margin and nature of seismicity in Eastern Folded Belt of Bengal Basin - Khan, Aftab Alam (Journal of Nepal Geological Society, 2004)
Tectogenesis of the eastern collision margin of the Indian plate is closely related to geodynamics and the nature of subduction. The oblique convergence and the anticlockwise rotation of the Indian plate have resulted in crustal and sub crustal segmentation of the converging plate having right-slip component to compensate the plate rotation. It is inferred that the crustal segmentations are the results of oblique convergence and the counter clockwise rotation of the Indian plate with that of clockwise rotation of the Burmese platelet. These segments have suffered right lateral movements in the form of torsion to compensate the rotational movements of the converging plates. Seismicity is intrinsically related to the tectonics of a region. Seismological analyses reveal that the regions of active seismic zones bear the signatures of the convergent plate boundary. The spatial distributions of earthquake events indicate two distinct (longitudinal and transverse) types of tectonic trends. The arc-shaped longitudinal trend follows the Indo-Burma orogen along 94°E longitude trending NE-SW in the north to NW- SE in the south, and two transverse trends having orientation ENE- WSW can be envisaged along 24°N and 22°N latitudes. Another trend is also observed along the NW-SE direction and eventually, merges with the tectonic trend TT3. The geological imprints, structural setting, and fault morphology as well as morpho -structural features of the Eastern Folded Belt (EFB) of the Bengal Basin bear the signature of active margin setting of the Indian plate, which is characterised by subduction-related accretionary wedges, and are internally deformed into various folds, faults, and thrusts. Six major seismic source zones namely: Frontal Himalaya source zone, Siwalik source zone. Dauki Fault source zone, EFB source zone, TT3 source zone, and Continental Slope source zone are identified in the Bengal Basin. Two decollment zones viz., intra-fold decollment at 5-6 km depth level and brittle-plastic transition at 10- 15 km depth level have been identified and they are characterised by shelf and pelagic mud sequences, respectively. These decollment zones act as lubricating agents for the reactivation of active faults. The thick mudrock sequences act as the zones of overpressure and lubrication under the maximum horizontal stress and the magnitude of tectonic stress regime. The accumulated strain when released during an earthquake can cause substantial damages. The Kolabunia earthquake of 2003 July 27 having moment tensor magnitude of 5.6 and focal depth of 11 km with its epicentre at Kolabunia (22°46' 18"N and 92°23'18"E) in the Rangamati District in the EFB is a typical inter-plate, or more precisely, a convergent plate margin earthquake. The focal mechanism solution provides the evidence of major thrust fault with strike slip component. The field evidence also supports that the dominant movement along the fault plane was thrust with strike slip component. The geophysical evidence of the Kolabunia earthquake indicates that the east-dipping detachment fault at brittle- plastic transition zone has initially triggered the earthquake and subsequently the movement along the intra-fold decollment has produced all surface ruptures and ground deformation.